2018
DOI: 10.5194/angeo-36-793-2018
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of mirror mode waves in sheath regions driven by interplanetary coronal mass ejection

Abstract: Abstract. We present a comprehensive statistical analysis of mirror mode waves and the properties of their plasma surroundings in sheath regions driven by interplanetary coronal mass ejection (ICME). We have constructed a semiautomated method to identify mirror modes from the magnetic field data. We analyze 91 ICME sheath regions from January 1997 to April 2015 using data from the Wind spacecraft. The results imply that similarly to planetary magnetosheaths, mirror modes are also common structures in ICME shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 67 publications
3
50
0
Order By: Relevance
“…It has been shown that a typical magnetic hole at 0.72 AU has an asymmetrical shape in the form of a rotational ellipsoid with major to minor axes ratio of 2.45:1 (Zhang, Russell, Baumjohann, et al, 2008). A separate analysis at 1 AU showed a consistent shape with the elongation ratio of 1.84:1, suggesting that MHs develop inside 0.72 AU and their shape is preserved in the solar wind (Xiao et al, 2010;Ala-Lahti et al, 2018;Baumgärtel, 1999). While Burlaga et al (2007) showed that the normalized size of MHs in the heliosheath is of the same order of magnitude as their size at 1 AU.…”
Section: Statistical Analysis Of Magnetic Holesmentioning
confidence: 93%
“…It has been shown that a typical magnetic hole at 0.72 AU has an asymmetrical shape in the form of a rotational ellipsoid with major to minor axes ratio of 2.45:1 (Zhang, Russell, Baumjohann, et al, 2008). A separate analysis at 1 AU showed a consistent shape with the elongation ratio of 1.84:1, suggesting that MHs develop inside 0.72 AU and their shape is preserved in the solar wind (Xiao et al, 2010;Ala-Lahti et al, 2018;Baumgärtel, 1999). While Burlaga et al (2007) showed that the normalized size of MHs in the heliosheath is of the same order of magnitude as their size at 1 AU.…”
Section: Statistical Analysis Of Magnetic Holesmentioning
confidence: 93%
“…Here n denotes the proton number density, k B the Boltzmann constant, B the local magnetic field strength and 0 the permeability of free space (Hasegawa, 1969). We note that a temperature anisotropy is the only likely generation mechanism for MM waves, and the interest in MM wave observations is less the mechanism of their generation but rather the origin of the generating temperature anisotropy (Ala-Lahti et al, 2018).…”
Section: Wave Generationmentioning
confidence: 99%
“…ICME sheaths also share some general properties of the fast solar wind (e.g., high fluctuation amplitudes) and slow wind (e.g., lower Alfvénicity). Plasma fluctuations found in ICME sheaths may comprise pre-existing fluctuations from the swept-up solar wind and fluctuations generated locally within the sheath, and may include a broad range of wave activity (e.g., Liu et al 2006;Ala-Lahti et al 2018;Ala-Lahti et al 2019). Global properties of the sheaths such as bulk flow speed can modify sheath turbulence properties, particularly in the kinetic range (Riazantseva et al 2019).…”
Section: Introductionmentioning
confidence: 99%